(untitled) (History Journal «Jerónimo Zurita», 2023)
The district of Cuenca was one of the four districts to which the sheepowners that were members of the “Mesta” and inhabited the mountainous regions of the kingdom belonged. The main urban centers of these regions were Cuenca and Molina de Aragón, that exercised jurisdiction over large territories. In this article the author pays attention to the social and political profile of these sheepowners. He identifies the members of the oligarchies of Cuenca and Molina that owned transhumant sheep, many of them of rural origin.And he proves that among the inhabirants of the rural areas there were several big and middle´rank ranchers, next to small owners and sheperds.